Inheritance tax planning at the end of life - Oscar Erixson; Sebastian Escobar (Uppsala University, Department of Economics, 2018)
There is a ongoing debate about whether inheritance and estate taxes are effective in raising revenues and in contributing to a more equal society. The different views on transfer taxes are largely dependent on beliefs about whether people plan their wealth to avoid these taxes. In this paper, we follow Kopczuk (2007) and study people's planning response to the onset of terminal illness. An extension of Kopczuk's work is that we can effectively control for responses in wealth caused by terminal illness but unrelated to tax planning. We do this by exploiting a tax reform in Sweden that removed the incentives for people to plan their estates to avoid inheritance taxation. We find some evidence of long-term terminal illness inducing responses consistent with tax planning, but that these are not widespread or efficient enough to reduce the overall tax burden in the study population. Our results, similarly to those of Kopczuk, show that people appear to postpone some decisions about their estates until shortly before death.
urn:nbn:se:uu:diva-346165
Keywords: H26; H31; D64; D14; 330; tax avoidance; tax evasion; tax reform; terminal illness